Biotinylated Photopolymers for 3D‐Printed Unibody Lab‐on‐a‐Chip Optical Platforms. Issue 1 (15th November 2017) - Credi, Caterina; Griffini, Gianmarco; Levi, Marinella; Turri, Stefano
Abstract: The present work reports the first demonstration of straightforward fabrication of monolithic unibody lab‐on‐a‐chip (ULOCs) integrating bioactive micrometric 3D scaffolds by means of multimaterial stereolithography (SL). To this end, a novel biotin‐conjugated photopolymer is successfully synthesized and optimally formulated to achieve high‐performance SL‐printing resolution, as demonstrated by the SL‐fabrication of biotinylated structures smaller than 100 µm. By optimizing a multimaterial single‐run SL‐based 3D‐printing process, such biotinylated microstructures are incorporated within perfusion microchambers whose excellent optical transparency enables real‐time optical microscopy analyses. Standard biotin‐binding assays confirm the existence of biotin‐heads on the surfaces of the embedded 3D microstructures and allow to demonstrate that the biofunctionality of biotin is not altered during the SL‐printing, thus making it exploitable for further conjugation with other biomolecules. As a step forward, an in‐line optical detection system is designed, prototyped via SL‐printing and serially connected to the perfusion microchambers through customized world‐to‐chip connectors. Such detection system is successfully employed to optically analyze the solution flowing out of the microchambers, thus enabling indirect quantification of the concentration of target interacting biomolecules. The successful application of this novel biofunctional photopolymer as SL‐material enables to greatly extend the versatility of SL to directly fabricate ULOCs with intrinsic biofunctionality. Abstract : A novel biotin‐conjugated photopolymer is synthesized to fabricate bioactive micrometric scaffolds directly embedded within monolithic unibody lab‐on‐a‐chip devices by means of multimaterial stereolithography. This is further exploited to fabricate a real‐time noninvasive optical detector for the quantification of the concentration of target biomolecules interacting within the biotinylated 3D microstructures.